Canine primary encephalopathies: a retrospective study of 48 cases (2008-2012) - POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. S.; ELEKIDOU (Ε. ΕΛΕΚΙΔΟΥ) E.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ) M. N.; BRELLOU (Γ. ΜΠΡΕΛΛΟΥ) G.; SOUBASIS (Ν. ΣΟΥΜΠΑΣΗΣ) N. (Journal of the Hellenic Veterinary Medical Society, 2017)
A retrospective study was performed on 48 dogs with primary encephalopathies, admitted during a 5-year period (2008-2012). Their age ranged from 2 months to 19 years, the majority being older than 10 years. Genders were almost equally distributed and most animals were purebreds or crossbreds. Onset of neurological signs was acute (11/48), subacute (12/48) or chronic (24/48). Lesion localization was focal in 31 and multifocal in 17 dogs. The cerebrum and brainstem were the most common focal localizations, while cerebellar lesions were recorded only in 4 dogs. An aetiologic diagnosis was established in 29 dogs and included primary (8/29) or metastatic neoplasia (2/29), encephalitis of variable etiology (9/29), congenital or inherited diseases (6/29), senile cognitive dysfunction (3/29) and ischaemic encephalopathy (1/29). In the remaining 19 dogs, aetiology of intracranial dysfunction was not determined; however a tentative diagnosis was speculated in eight of these cases and included breed specific and viral encephalitis, neoplasia, ischaemic encephalopathy and inherited disease. Most dogs were euthanized due to the debilitating neurological signs (24/48) or died from complications of their illness (13/48). Six animals are still alive with symptomatic medical treatment and supportive nursing care and 5 were lost to follow up.